THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. GEMILANG NUSANTARA INSANI SELATAN TANGERANG - Monica Monica; Henni Marlinah (Jurnal Scientia, 2023)
This research aims to investigate the influence of the work environment and work motivation on employee performance at PT Gemilang Nusantara Insani, South Tangerang. An associative research method with a quantitative approach was employed. The study included a population of 60 respondents. The analysis involved validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests, simple linear regression tests, multiple linear regression tests, correlation coefficients, coefficient of determination, T-tests, and F-tests. The results of partial hypothesis testing revealed that the work environment variable had a positive effect on employee performance, with a t-value of 5.385, and a significance value of 0.000. Similarly, the work motivation variable had a significant impact on employee performance, with a t-value of 5.704 and a significance value of 0.000. Simultaneous hypothesis testing indicated that the work environment and work motivation, taken together, significantly influenced employee performance, as the calculated F-value (20.916) was greater than the F-table value (3.16), with a significance value of 0.000. The coefficient of determination (R square) was 0.423, suggesting that the combined influence of the work environment and work motivation accounted for 42.3% of the variance in employee performance. The remaining 57.7% was influenced by factors not examined in this study. In conclusion, both the work environment and work motivation have a significant and positive impact on employee performance at PT Gemilang Nusantara Insani, South Tangerang.